Effect of Vacuum and Non-Vacuum Packaging Combined with Cold Storage on the Shelf Life of Smoked Komo Mackerel (Euthynnus affinis) - Maryati Maryati; M. Fathur Khairat Rumatoras; Reski Rahman Sriwijaya (Nekton, 2025)
Smoking is a post-harvest processing technique used to extend the shelf life and maintain the quality of fish products. In Fakfak Regency, smoked fish products are generally marketed without adequate packaging, making them prone to quality deterioration. This study aimed to evaluate the effects of packaging type (vacuum and non-vacuum), cold storage duration (4 °C), and their interaction on moisture content, pH, water activity (Aw), and organoleptic characteristics of smoked Komo mackerel (Euthynnus affinis). The experiment employed a two-factor Completely Randomized Design (CRD), with factors being packaging type (vacuum and non-vacuum) and cold storage duration (days 7, 11, 17, and 25), each treatment replicated three times. Quantitative data were analyzed using SPSS version 27 using GLM Multivariate while factor interactions were analyzed using One-Way ANOVA. If significant differences were found, further testing was performed using Duncan's Multiple Range Test (DMRT) (p < 0.05). Organoleptic data were descriptively evaluated based on color, texture, and aroma. The results indicated that the combination of vacuum and non-vacuum packaging with cold storage (4 °C) significantly affected moisture content, pH, and Aw. The interaction between the two factors was only significant for moisture content and pH, while the effect on Aw was not significant. Organoleptic observations showed that vacuum packaging was able to maintain product quality until day 24, whereas non-vacuum packaging showed quality deterioration from day 11, characterized by pale brown color, soft texture, and loss of characteristic smoked fish aroma. In conclusion, vacuum packaging is more effective in extending the shelf life and maintaining the quality of smoked Komo mackerel compared to non-vacuum packaging under cold storage conditions.